Step-by-step explanation:
Here we have the following expression:
![2(n - 1) + 1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/thme8qf4qjo4lvrdqvzu15428uhsmv74id.png)
So we can rewrite this as follows:
![a_(n)=2(n - 1) + 1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/xer7amk9j7swszghj5mvprisqhc311o1p8.png)
So this is an arithmetic series whose general form is given by:
![a_(n) = a + d(n-1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/9vug7pt66gdvet8c29q0bb7gw7biyw497j.png)
Where:
![a: \text{is the first term} \\ \\ d: \text{is the difference between the terms, also called](https://img.qammunity.org/2021/formulas/mathematics/middle-school/kmhyav79sk79kw3ogh0zohufxsfrkc8x4j.png)
So, for some n-values we have:
![a=1 \\ \\ a_(2)=2(2-1)+1=3 \\ \\ a_(3)=2(3-1)+1=5 \\ \\ a_(4)=2(4-1)+1=7 \\ \\ a_(5)=2(5-1)+1=9](https://img.qammunity.org/2021/formulas/mathematics/middle-school/cogf2etiubjsprcsx6zegh51lk288t3ymd.png)
From this information, the diagram that best represents the given expression is shown below.